Effect of Curcumin gel on inflammatory and anti-inflammatory biomarkers in experimental induced periodontitis in rats: a biochemical and immunological study - Mohammad, Chenar Anwar; Ali, Khadeeja Mohammed; Sha, Aram Mohammed; Gul, Sarhang Sarwat (Frontiers in Microbiology, 2023)
This study aimed to determine the effect of local application of curcumin gels as adjunct to scaling and root planing (SRP) on the inflammatory biomarkers matrix metalloproteinase-8 (MMP-8), interleukin-6 (IL-6), C-reactive protein (CRP), and alkaline phosphatase (ALP), and the anti-inflammatory biomarker interleukin-10 (IL-10) in rats with experimentally induced periodontitis. Fifty-five adult Wistar rats with experimentally induced periodontitis were randomly divided into four groups: 15 rats received SRP + curcumin gel (CU), 15 rats received SRP + Tetracycline gel (Tet), 15 rats were treated with SRP alone, and 5 rats had experimental periodontitis without treatment (EP). Five systemically healthy rats without experimental periodontitis were used as the controls. Blood samples were collected by cardiac puncture from all groups after 2, 4, and 6 weeks of therapy. Biomarker levels determined by enzyme-linked immunosorbent assay (ELISA) and, ANOVA were used to compare the study groups. The results showed a significant increase in pro-inflammatory biomarkers and a significant decrease in anti-inflammatory biomarkers in the EP group compared with the control group (p < 0.05). The local application of curcumin or tetracycline gels resulted in a significant reduction in all inflammatory biomarkers at all periods of examination compared to the EP group. IL-10 levels gradually increased after 2 weeks, peaked at 4 weeks, and then decreased after 6 weeks, however, Tet showed statistically significant improvement compared to CU (p < 0.05). Adjunctive application of CU gel was as effective as Tet gel in the treatment of EP in rats by reducing inflammatory biomarkers and enhancing anti-inflammatory cytokines.